2004
DOI: 10.1128/jvi.78.19.10213-10220.2004
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Intestinal and Systemic Rotavirus Infection

Abstract: Rotaviruses are responsible for significant gastrointestinal disease, primarily in children Ͻ5 years of age and the young of other mammalian species. Each year rotaviruses cause approximately 111 million episodes of gastroenteritis in children, which result in 25 million visits to clinics, 2 million hospitalizations, and 352,000 to 592,000 deaths. On a worldwide basis, nearly every child experiences rotavirus gastroenteritis by age 5, 1 in 5 visits a clinic, 1 in 65 is hospitalized, and 1 in 293 dies. Children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
230
0
33

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(275 citation statements)
references
References 74 publications
3
230
0
33
Order By: Relevance
“…IEC of the small intestine are the primary site of virus replication. 95 It has been shown that IgA is important for clearance of a primary infection and for protection from reinfection in mice. 96 In humans, IgA is a good correlate of protection against Rotavirus infection, but multiple infections can occur during the lifetime of the host.…”
Section: Functions Of Igamentioning
confidence: 99%
“…IEC of the small intestine are the primary site of virus replication. 95 It has been shown that IgA is important for clearance of a primary infection and for protection from reinfection in mice. 96 In humans, IgA is a good correlate of protection against Rotavirus infection, but multiple infections can occur during the lifetime of the host.…”
Section: Functions Of Igamentioning
confidence: 99%
“…The rotavirus is genetically comprised of 11 segments of dsRNA (9). The purified genomic dsRNA from rotavirus or reovirus are recognizable by TLR3 (10,11), suggesting that genomic dsRNA and TLR3 signaling may be involved in viral pathogenesis.…”
mentioning
confidence: 99%
“…However, to reduce the RV-associated acute GE (AG) worldwide, RV vaccines are developed and in 2009, WHO recommended to include prophylactic RV vaccination for infants in all national immunization programs. [2] These vaccines proved efficacy against the viruses such as G and P types (G1, G2, G3, G4, G9 and P [4], P [6], P [8]) that are circulating worldwide and leads to approximately 90% of the disease [7] From the previous studies, it was shown that vaccine efficacy in highly income countries is more than that in middle and low income countries. [8] Alt hough there is lesser effects in middle income settings, these vaccines when introduced into national immunization programs has been associated with a significant decrease in AG-related deaths.…”
Section: Introductionmentioning
confidence: 99%
“…Since the bolus is osmotically active, the colon cannot able to absorb required water and therefore results in diarrhea. [4] RV diarrhea also causes enterocyte destruction and villus ischemia. Immunity develops with each infection, meaning, subsequent infection is less severe.…”
Section: Introductionmentioning
confidence: 99%